Sigismundus Laetus – Žygimantas Liauksminas? On Some Mysterious Addressees of Sarbievius’s Odes - Daukšienė, Ona (Senoji Lietuvos literatūra, 2017)
The paper raises the issues of identification of so far unknown or little known addressees of poetry by Mathias Casimirus Sarbievius (Maciej Kazimierz Sarbiewski, 1595–1640), or of revision of information about them. Neither Lithuanian nor Polish scholars have achieved much in this field during the past decades: since Krystyna Stawecka’s paper on the addressees of Sarbievius’ poetry (1975), the data has not been updated with some exceptions, including specifications made by Józef Warszawski SJ (1984) and information on Wojciech Turski (Albertus Turscius), the addressee of Ode IV. 32, in a recent paper by Wojciech Ryczek (2016).Therefore in the present study attention was focused on two groups of addressees of Sarbievius’s lyrical poetry. The first group consisted of his friends or fellow-students, mostly Jesuits, the information about whom is scarce, while the second group included individuals referred to in pseudonyms that have not been identified yet and who, in the opinion of earlier scholars, could be fictitious. In the effort to find out whether the supposedly real friends of the poet did not hide behind these pseudonyms, the yet-unidentified addressee of Ode IV. 11 named by the pseudonym of Sigismundus Laetus, was identified. It was Žygimantas Liauksminas SJ (Sigismundus, Zygmunt Lauxmin SJ, 1587/98–1670), the author of well-known works on rhetoric and music theory and a future vicerector of Vilnius University. According to some sources, his risible nature had earned him the nickname ‘Tėvas Linksmas’ (‘Father Joyful’, in the Latin laetus). He was several years younger than Sarbievius and, correspondingly, entered the novitiate in Vilnius later, but it was at Vilnius Academy that during certain stages of their studies their paths crossed. This happened between 1620 and 1622, when Liauksminas was studying philosophy and Sarbievius was a student of theology; also, between 1627 and 1629, when the former continued and then successfully completed his studies of philosophy, and the latter was teaching rhetoric and philosophy. The characteristic of Liauksminas in the reference of his tertianship (1629–1630, written by Laurentius Bartilius SJ in 1630) found in Liber provincialis, about how he could not often suppress laughter, matches the nickname ‘Father Joyful’ mentioned in other sources. Associations with Sarbievius’ Ode IV. 11 can be discerned in this reference. The author recommends the addressee to maintain silence (silentium commendat); from the position of an older companion (socius), he offers well-meant advice on despising vain glory, avoiding fame and the favour of the crowd. (The above-mentioned characteristic mentions Liauksminas’ certain ‘not completely suppressed’ habits and points out that he is open to a warning and adequately receptive to criticism addressed to him.) Up until now, Sigismundus Laetus, the addressee of Ode IV. 11, has been referred to as a fictitious or anonymous individual both by Polish and Lithuanian scholars. The approximate date of the composition of this ode was presumed to be between 1628 and 1631, which almost coincides with the documented dates of communication of the two famous Jesuits of the Lithuanian province. In this paper, however, it is proposed that the later date should be moved to 1630 or even to 1629.In addition, the paper provides additional information on Wojciech Turski, the addressee of Ode IV. 32. Very likely he met Sarbievius at Polotsk College in 1626–1627 when they both taught there: Turskis was in charge of the grammar class and Sarbievius taught rhetoric. There is no doubt that from 1628 they communicated in Vilnius: from 1628 to 1631, Sarbievius must have been Turski’s professor in philosophy, and from 1632 to 1635 he taught theology. According to Liber provincialis, on 2 June 1631 Turski took an examination in metaphysics and received the highest grades in his course, and Sarbievius was one of the examiners. The paper raises a hypothesis that the themes of the ode dedicated to Turski (dreams, poetry, and flight) were not incidental, and that the ode might have been written in 1631.A conclusion is drawn that Sarbievius’ poetical works dedicated to the abovementioned and other identified or implied fellow Jesuits comprise a common thematic field that encompasses the elements of Jesuit spirituality, poetical representations of the significance of vows, treasured friendship of the socii, or companions, the motifs of the importance of well-meant advice for spiritual advancement, and the like. This conclusion opens possibilities to expand the existing interpretations of Sarbievius’ verses, because it is this particular type of his work that is often and rather one-sidedly treated as merely adaptations of Horatian patterns or, for instance, as presentation of stoicism ideas.
Keywords: Mathias Casimirus Sarbievius; Maciej Kazimierz Sarbiewski; NeoLatin literature – 17th century; Society of Jesus; jesuit creativity; addressees; Žygimantas Liauksminas; Sigismundus Lauxmin; Sigismundus Laetus; Wojciech Turski; Albertus Turscius; Laevinius Hielius